(untitled) (Mantichora. Italian Journal of Performance Studies, 2026)
The relationship that Paolo Gioli establishes between his artistic production and the body is the cornerstone of his creative research. This connection, combined with a subversive use of photographic and filmic apparatuses, allows him to emerge as a peculiar figure within the contemporary artistic landscape. The experimentation carried out by the visual artist advances a deeply incisive approach to the body and, opening up to the most diverse possibilities of manipulation, draws it into a regressive path that forces it into a new identity: that of a “body-object”.